2022
DOI: 10.1038/s41598-022-11517-w
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of acute necrotizing pancreatitis by artificial intelligence: a prospective cohort-analysis of 2387 cases

Abstract: Pancreatic necrosis is a consistent prognostic factor in acute pancreatitis (AP). However, the clinical scores currently in use are either too complicated or require data that are unavailable on admission or lack sufficient predictive value. We therefore aimed to develop a tool to aid in necrosis prediction. The XGBoost machine learning algorithm processed data from 2387 patients with AP. The confidence of the model was estimated by a bootstrapping method and interpreted via the 10th and the 90th percentiles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…However, these clinical laboratory items are likely to fail considering they are not specific for the complex pathophysiology of NP. A research team recently used machine learning strategy to process data from 2387 AP patients measured in the first 24h of clinical admission ( 36 ). They released an on-admission prediction model for NP online which stressed the impacts of gender, total white blood cell count, glucose, alkaline phosphatase, and CRP.…”
Section: Discussionmentioning
confidence: 99%
“…However, these clinical laboratory items are likely to fail considering they are not specific for the complex pathophysiology of NP. A research team recently used machine learning strategy to process data from 2387 AP patients measured in the first 24h of clinical admission ( 36 ). They released an on-admission prediction model for NP online which stressed the impacts of gender, total white blood cell count, glucose, alkaline phosphatase, and CRP.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al [ 155 ] demonstrated that the XGBoost algorithm possesses the capability to precisely predict the severity of AP, offering clinicians valuable assistance in identifying severe AP at an early stage. In a prospective cohort study integrating necrosis prediction with AI, the XGBoost machine learning algorithm was employed to analyze the data from 2387 AP patients[ 156 ]. This model in the predictive capability rivals those existing clinical scoring systems, and its performance is anticipated to improve with continued use[ 156 ].…”
Section: Aimentioning
confidence: 99%
“…In a prospective cohort study integrating necrosis prediction with AI, the XGBoost machine learning algorithm was employed to analyze the data from 2387 AP patients[ 156 ]. This model in the predictive capability rivals those existing clinical scoring systems, and its performance is anticipated to improve with continued use[ 156 ]. In the United States, Thapa et al [ 7 ] applied machine learning algorithms to predict which AP patients need SAP treatment and developed three models using logistic regression, neural networks, and XGBoost.…”
Section: Aimentioning
confidence: 99%
“…AP is an inflammatory condition, thus exhibiting systemic manifestations of inflammation, including fever, tachycardia, hypotension, elevated white blood cell count (WBC), and increased levels of C-reactive protein (CRP) [5][6][7]. These characteristics do not differentiate between inflammation and infection, leading to an excessive utilization of antibiotics across the entire range of disease severity without distinguishing between the two [8].…”
Section: Introductionmentioning
confidence: 99%